2015
DOI: 10.1007/s00261-015-0438-4
|View full text |Cite
|
Sign up to set email alerts
|

CT textural analysis of hepatic metastatic colorectal cancer: pre-treatment tumor heterogeneity correlates with pathology and clinical outcomes

Abstract: CT texture features, particularly entropy, MPP, and SD, are significantly associated with tumor grade in untreated CRC liver metastases. Tumor entropy at coarse filters correlates with overall survival. Single-slice 2D texture analysis appears to be adequate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
170
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(183 citation statements)
references
References 28 publications
12
170
1
Order By: Relevance
“…Despite the need for further validation sets, this study provides a basis for additional research (e.g using PET-CT features) that could improve performance. We believe such radiomics based analyses can be used as a complementary method of patient stratification for NSCLC prior to the initiation of therapy as is currently being investigated in other disease sites such as breast [35,36], colorectal cancer [37], and glioblastoma [38]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the need for further validation sets, this study provides a basis for additional research (e.g using PET-CT features) that could improve performance. We believe such radiomics based analyses can be used as a complementary method of patient stratification for NSCLC prior to the initiation of therapy as is currently being investigated in other disease sites such as breast [35,36], colorectal cancer [37], and glioblastoma [38]. …”
Section: Discussionmentioning
confidence: 99%
“…However, several studies have shown that use of a single slice is sufficient for sampling and extracting subtle features relevant for the clinical application being evaluated [22,40]. In addition, the cohort was a pooled group of liver disease with a variety of etiologies included.…”
Section: Discussionmentioning
confidence: 99%
“…This additional evaluation of segments I-III versus IV-VIII was based on the morphologic changes seen in cirrhosis and prior work looking at the liver segmental volume ratio (LSVR) [15,16]. Previous studies have demonstrated that CTTA from a single-slice analysis have demonstrated the ability to extract sufficient information related to answer the clinical question and may not require multi-slice or volume analysis which have not shown to add significant benefit to the clinical application being researched (22,36). Furthermore single-slice analysis reduces the computational time (is more practical in a routine radiological workflow) and complexities associated with multi-slice/volumetric analysis related to operator variability associated with ROI drawing particularly if the ROI drawing process involves manual/semi-automated segmentation approaches.…”
Section: Ct Texture Analysis (Ctta)mentioning
confidence: 99%
See 1 more Smart Citation
“…TA has been used to distinguish gastric cancer subtypes 19 and to predict OS in patients with primary colorectal cancers, 20 hepatocellular carcinoma, 21 and CRLM. 22 In patients with CRLM, tumor morphology assessed by radiologists correlated with pathologic response and survival, suggesting a link between imaging, pathology, and survival, but this relationship has not been well-elucidated. 23 …”
Section: Introductionmentioning
confidence: 99%